2010
DOI: 10.3354/dao02260
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of disease caused by Francisella sp. in Nile tilapia Oreochromis niloticus at a recirculation fish farm in the UK

Abstract: This study details the first diagnosis of Francisella sp. in tilapia in the United Kingdom. Losses of tilapia fry at a recirculation fish farm in England were investigated, giving a presumptive positive diagnosis of infection with Francisella sp. by histopathological examination. Most fish sampled showed moderate to marked pathology of the major organs, with lesions being present in most tissues. The most obvious host response was granuloma formulation. A subsequent follow-up visit provided further evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 11 publications
3
44
1
Order By: Relevance
“…Our results are consistent with those of previous studies, which showed that Nile tilapia fingerlings are the life stage most susceptible to FNO infection (Jeffery et al, 2010;Soto et al, 2011Soto et al, , 2013. In addition, the occurrence of disease in young adult tilapia (>100g) was confirmed.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our results are consistent with those of previous studies, which showed that Nile tilapia fingerlings are the life stage most susceptible to FNO infection (Jeffery et al, 2010;Soto et al, 2011Soto et al, , 2013. In addition, the occurrence of disease in young adult tilapia (>100g) was confirmed.…”
Section: Discussionsupporting
confidence: 83%
“…The diseased fish presented with anorexia, melanosis, exophthalmia, erratic swimming, skin ulcers, and gill pallor. These clinical signs were similar to previously described outbreaks of FNO-related francisellosis in tilapia in Central America (Mauel et al, 2007;Soto et al, 2009), Taiwan (Chen et al, 1994), Indonesia (Ottem et al, 2009), the UK (Jeffery et al, 2010), and the USA (Soto et al, 2011). Our findings represent the first report of outbreaks of FNO-related francisellosis in South America.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…RASs improve conditions for cultured fish by having greater control over environmental and water quality parameters and enhancement of feeding efficiency. Subsequently, RASs can allow for higher stocking densities than most aquacultural systems [91,100,[104][105][106][107][108][109][110] by sterilizing the water prior to (re)entry to the fish tanks, pathogens and contaminants are removed, reducing the risk of disease outbreaks and contaminant uptake by the fish [18,104,111]. Due to the on-land and recirculatory nature of RASs, the potential for fish escapes is greatly reduced [2,104].…”
Section: Recirculating Aquaculture Systems (On-land)mentioning
confidence: 99%